Development of loop-mediated isothermal amplification (LAMP) assay using SYBR safe and gold-nanoparticle probe for detection of Leishmania in HIV patients - Toon Ruang-areerate (Nature Portfolio, 2021)
Abstract Asymptomatic leishmaniasis cases have continuously increased, especially among patients with HIV who are at risk to develop further symptoms of cutaneous and visceral leishmaniasis. Thus, early diagnosis using a simple, sensitive and reliable diagnostic assay is important because populations at risk mostly reside in rural communities where laboratory equipment is limited. In this study, the highly sensitive and selective determination of Leishmania infection in asymptomatic HIV patients was achieved using dual indicators (SYBR safe and gold-nanoparticle probe; AuNP-probe) in one-step LAMP method based on basic instruments. The assay can be simply evaluated under the naked eye due to clear interpretation of fluorescent emission of LAMP-SYBR safe dye-complex and colorimetric precipitate of specific AuNP-probes. The sensitivities and specificities of fluorescent SYBR safe dye and AuNP-probe indicators were equal, which were as high as 94.1 and 97.1%, respectively. Additionally, detection limits were 102 parasites/mL (0.0147 ng/µL), ten times more sensitivity than other related studies. To empower leishmaniasis surveillance, this inexpensive one-step SYBR safe and AuNP-LAMP assay is reliably fast and simple for field diagnostics to point-of-care settings, which can be set up in all levels of health care facilities including resource limited areas, especially in low to middle income countries.